Engineering Escherichia coli for anaerobic alkane activation: Biosynthesis of (1‐methylalkyl)succinates. Issue 1 (16th October 2021) - Wang, Yixi; Nguyen, Nam; Lee, Seung H.; Wang, Qinxuan; May, Jeremy A.; Gonzalez, Ramon; Cirino, Patrick C.
Abstract: In anoxic environments, microbial activation of alkanes for subsequent metabolism occurs most commonly through the addition of fumarate to a subterminal carbon, producing an alkylsuccinate. Alkylsuccinate synthases are complex, multi‐subunit enzymes that utilize a catalytic glycyl radical and require a partner, activating enzyme for hydrogen abstraction. While many genes encoding putative alkylsuccinate synthases have been identified, primarily from nitrate‐ and sulfate‐reducing bacteria, few have been characterized and none have been reported to be functionally expressed in a heterologous host. Here, we describe the functional expression of the (1‐methylalkyl)succinate synthase (Mas) system from Azoarcus sp . strain HxN1 in recombinant Escherichia coli . Mass spectrometry confirms anaerobic biosynthesis of the expected products of fumarate addition to hexane, butane, and propane. Maximum production of (1‐methylpentyl)succinate is observed when masC, masD, masE, masB, and masG are all present on the expression plasmid; omitting masC reduces production by 66% while omitting any other gene eliminates production. Meanwhile, deleting iscR (encoding the repressor of the E. coli iron–sulfur cluster operon) improves product titer, as does performing the biotransformation at reduced temperature (18°C), both suggesting alkylsuccinate biosynthesis is largely limited by functional expression of this enzyme system. Abstract : A methyl‐alkylsuccinate synthase system from a denitrifying bacterium was functionally expressed in Escherichia coli, enabling the anaerobic activation of alkanes, via fumarate addition. Four genes were essential to this activity. These results establish a metabolic engineering platform for oxygen‐independent activation and bioconversion of alkanes in E. coli.